An investigation of teacher‐trainers’ perceptions of Indonesian English, proficiency in English, and training practices in West Sumatra, Indonesia - Imelwaty, Sri (Curtin University, 2014)
This study investigated teacher-trainers’ perceptions of the construct ‘proficiency in English’, and the manifestation of the perceptions in training practices. The degree of fit between perceptions and practices was discussed to inform English language teaching pedagogy with respect to the development of a distinctly Indonesian variety of English. A sequential mixed method research design underpinned this study. The research was conducted in West Sumatra province, Indonesia. Research findings indicated the gaps between perceptions and practices.